2018
DOI: 10.1021/acs.biochem.8b01033
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Caenorhabditis elegans Nucleosome Assembly Protein 1 Uncovers the Role of Acidic Tails in Histone Binding

Abstract: Nucleosome assembly proteins (Naps) influence chromatin dynamics by directly binding to histones. Here we provide a comprehensive structural and biochemical analysis of a Nap protein from Caenorhabditis elegans (CeNap1). CeNap1 naturally lacks the acidic Nterminal tail and has a short C-terminal tail compared to many other Nap proteins. Comparison of CeNap1 with full length and tail-less constructs of Saccharomyces cerevisiae Nap1 uncovers the role of these tails in selfassociation, histone binding, and Nap co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Our complex structure shows that only one copy of H2A-H2B heterodimer binds a headphone-like ceNAP1 homodimer at one earmuff domain (one side of the concave surface) of the ceNAP1 homodimer (Fig- ure 3B). The 1:1 molar ratio was consistent with the recent biochemical characterization of full-length ceNAP1 at 300 mM NaCl (Sarkar et al, 2019). The molar ratio of our complex structure is the same as that reported previously in the low-resolution scNAP1-H2A-H2B complex (Aguilar-Gurrieri et al, 2016).…”
Section: The Acidic Concave Surface Of Cenap1 Is Important For Tetramerizationsupporting
confidence: 91%
See 3 more Smart Citations
“…Our complex structure shows that only one copy of H2A-H2B heterodimer binds a headphone-like ceNAP1 homodimer at one earmuff domain (one side of the concave surface) of the ceNAP1 homodimer (Fig- ure 3B). The 1:1 molar ratio was consistent with the recent biochemical characterization of full-length ceNAP1 at 300 mM NaCl (Sarkar et al, 2019). The molar ratio of our complex structure is the same as that reported previously in the low-resolution scNAP1-H2A-H2B complex (Aguilar-Gurrieri et al, 2016).…”
Section: The Acidic Concave Surface Of Cenap1 Is Important For Tetramerizationsupporting
confidence: 91%
“…Our SEC-MALS experiments of ceNAP1 C -xgH2A-gH2B (Figure S4A) (or ceNAP1 C -ceH2A-H2B, Figure S4B) at 200 mM NaCl showed that the average MW of the ceNAP1 C -H2A-H2B complex is larger than its theoretical MW, indicating the presence of oligomers (ceNAP1-H2A-H2B) n . These are consistent with previous SEC-MALS data of full-length ceNAP1-H2A-H2B at 150 mM NaCl (Sarkar et al, 2019). The oligomer states of ceNAP1 C -xgH2A-xgH2B were further investigated at 200 mM NaCl using AUC-SV.…”
Section: The Acidic Concave Surface Of Cenap1 Is Important For Tetramerizationsupporting
confidence: 89%
See 2 more Smart Citations
“…NAP1, initially obtained from Xenopus laevis eggs and identified as a protein that facilitates the in vitro assembly of nucleosomes, is conserved extensively across different species (Laskey et al 1978). NAP family proteins have been reported from a wide range of organisms, such as yeast (Ishimi and Kikuchi 1991), Plasmodium (Gill et al 2009), Drosophila (Ito et al 1996), Xenopus (Steer et al 2003), human (Li et al 2016), Caenorhabditis elegans (Sarkar et al 2019), soya bean (Yoon et al 1995), rice (Dong et al 2003), tobacco (Dong et al 2003), and Arabidopsis (Liu et al 2009). The representative members of NAP family include Vps75 in yeast (Berndsen et al 2008;Tang et al 2008), hsNAPIL and xlNAPIL in human and Xenopus laevis, respectively, SETα and SETβ in humans and metazoans, and NAP1 related protein 1 (NRP1) and NAP1 related protein 2 (NRP2) in A. thaliana (Zhu et al 2006).…”
Section: Nucleosome Assembly Proteinsmentioning
confidence: 99%